Local People’s Perception regarding Tourism Development: The Case of Yogyakarta, Indonesia - HENDIJANI, Roozbeh Babolian; Yuliana, Yuliana (Journal of Environmental Management and Tourism, 2016)
The development of tourism is viewed as a source of new job opportunities, foreign exchanges, additional taxes, and regional development. Although residents’ perception toward tourism has significantly influenced tourism development, still there is a lack of academic studies in Indonesia to show the support of tourism by the local community. The purpose of this research is to determine the cultural, economic, and environmental effects of tourism on the culture of the local people in Yogyakarta, Indonesia. A qualitative approach through face-to-face interviews conducted to know the viewpoints of local people from Yogyakarta. The findings propose new insights into the different impacts of tourism and community development practices. These findings show the positive and negative aspects of tourism on the local community. This study concludes that although the host population perceives different point of views with tourism development, overall the Yogyakarta residents are happy about the economic benefits it brings to their community. Finally, the results of this research present some managerial implications and practical information for both the Ministry of Tourism and stakeholders in the tourism industry.
Keywords: tourism; local community; perception; Yogyakarta